Design and Performance Evaluation of a Three-Phase Self-Excited Induction Generator Feeding Single-Phase Loads. Issue 6 (21st April 2019) - Abdel-Aziz, Aly A.; Hamdy, Ragi A.; Abdel-Khalik, Ayman S.
Abstract: In this article, the performance of a three-phase delta connected self-excited induction generator (SEIG) using only two capacitors and feeding a single-phase load is investigated under both dynamic and steady state conditions. Two simple formulas are derived to design the required values of the excitation capacitors that not only result in balanced stator phase currents under full load, but also eliminate the induced torque pulsation due to single phase loading. The dynamic model of the proposed connection in the stationary αβ0 reference frame is also introduced and used to simulate different operational cases. The effect of core losses is included in the analysis to improve the efficiency estimation using a shunt equivalent core loss resistance. The system model is built and simulated using MATLAB/SIMULINK. The simulation results are presented and experimentally verified under different loading conditions.